Importance and applications of DOE/optimization methods in PEM fuel cells: A review - Karanfil, Gamze (International journal of energy research, 2020)
Summary Although proton exchange membrane (PEM) fuel cells are seen as one of the energy conversion technologies of the future due to their high energy conversion efficiency, low levels of emissions, low temperature operation, and compact systems, studies continue to reduce their cost, which is the biggest obstacle to commercialization. Design of experiment (DOE) methods are frequently used in optimization of PEM fuel cells to reduce their cost by decreasing experimental runs. This paper reviews the main gains subsuming the usage of several DOE and optimization methods in PEM fuel cell components, design, operation conditions, and model parameters. It firstly focuses on the Taguchi method and response surface methodology (RSM) known to be applied usually in PEM fuel cell studies. In addition to these known methods, other experimental design and optimization methods used in PEM fuel cells are discussed, and the results are summarized. This manuscript showed that the use of DOE and optimization methods in each working area of the PEM fuel cell, such as understanding the operating principle, elucidating the relationship between the components, determining the optimum conditions in the production and design of the components, and deciding the operating conditions of the single cell or stack system, are important in both increasing efficiency and lowering the cost.